Anthropometry, Body Composition, and Performance in Sport-Specific Field Test in Female Wheelchair Basketball Players - Cavedon, Valentina; Zancanaro, Carlo; Milanese, Chiara (Frontiers in Physiology, 2018)
Data on the physical and performance characteristics of female wheelchair basketball (WB) players are scarce. In several countries female WB players train and compete with male players on mixed teams due to the limited total population of players, which would otherwise lead to large territorial spread for each team. Any differences in terms of physical characteristics and/or WB skill proficiency between male and female WB players would be relevant to team performance in mixed teams. This work examined anthropometry, body composition and performance in a set of sport-specific field tests in a sample of 13 female WB players representing about 40% of the eligible population in Italy across a range of functional ability points (Point). Point is assigned on an ordinal scale from 1.0 (i.e. players with minimal functional potential) through to 4.5 (players with maximum functional potential). Our female sample was then compared against twice as many (n=26) Point-matched (±0.5 Points) male players. The two groups were similar for age (P=0.191; effect size [d]=0.2), self-reported duration of injury (P=0.144, d=0.6), WB experience (P=0.178, d=0.5), and volume of training (P=0.293, d=0.4). The large majority of measured linear anthropometric variables (10/13) were lower in female players than males (0.001<P≤0.041). Skinfold-estimated percent body fat was higher (+7.6%) in females (30.7±6.0%; P<0.001, d=1.3). Mean performance was worse in female than in males in six out of seven sport-specific field tests, scores being significantly lower in females for the maximal pass (7.5±2.0m for females vs. 10.4±2.8m for males; P=0.002, d=1.2) and suicide tests (55.8±6.4s for females vs. 45.4±6.7s for males; P<0.001, d=1.6). When performance in subgroups of females (n=9) chosen across a range of Point was compared with that of males assigned 1.0 or 1.5 Point less (each n=9), performance differences between male and female WB players were partially and completely eliminated, respectively. This work contributed new data for characterizing the physique and performance of female WB players. Further, the results suggested that when male and female athletes compete together in mixed teams, a 1.5 points subtraction from female players is needed to match the real gender difference in performance.